Cytotoxic Effect of the Genus Sinularia Extracts on Human SCC25 and HaCaT Cells - Guey-Horng Wang; Tzung-Han Chou; Rong-Jyh Lin; Jyh-Horng Sheu; Shih-Hao Wang; Chia-Hua Liang (Journal of Toxicology)
Soft corals of the genus Sinularia are being increasingly adopted to treat a wide variety of disease processes. However, the mechanism underlying its activity against human oral cancer cells is poorly understood. This study evaluates the cyototoxicity effects of the genus Sinularia extracts (S. grandilobata, S. parva, S. triangula, S. scabra, S. nanolobata and S. gibberosa) by SCC25 and HaCaT cells. The cell adhesion assay indicates that extracts reduce the cell attachment. Extracts exhibit a dose-dependent cytotoxic effect using MTS assay.Treatment of extracts to observe the morphological alterations in cells, membrane blebbing, nuclear condensation, and apoptotic bodies is demonstrated. Flow cytometry shows that extracts sensitized the cells in the G0/G1 and G2/M phases with a concomitant significantly increased sub-G1 fraction, suggesting cell death by apoptosis. Extracts of the genus Sinularia thus apparently cause apoptosis of SCC25 and HaCaT cells, and warrant further research investigating the possible antioral cancer compounds in these soft corals.